Engineering-Based Tornado Damage Assessment: Numerical Tool for Assessing Tornado Vulnerability of Residential Structures - Jain, Anant; Bhusar, Arpit A.; Roueche, David B.; Prevatt, David O. (Frontiers in Built Environment, 2020)
Following a series of deadly tornadoes between 2011, this paper develops a numerical tool to help communities better predict and quantify the potential tornado damage to single-family residential structures from a tornado strike. The objective is to determine the predictive capability of an engineering-based tornado damage-assessment (ETDA) Tool using published building damage observations captured by the authors in two recent tornadoes. The research is motivated by the need for the public to visualize the extent of tornado vulnerabilities of residential buildings in our communities. The research developed a numerical estimation model to aggregate damage that a specified tornado would cause to the residential wood-framed structures in a community. The ETDA Tool was developed around a Monte Carlo simulation engine, using theoretical models for tornado wind velocity and pressure drop in the tornado vortex, as well as experimentally-determined probability distribution functions for the structural resistances of eight building component systems selected to describe the structure. The output of the EDTA Tool is presented as series of mean damage ratios, and other statistics quantifying tornado-damage caused plotted against distance away from the tornado vortex centerline. The paper explains the methodology of the approach and present results comparing hindcast damage ratios against observed values of field-observations collected after a tornado strike on residential communities in Garland/Rowlett, TX. It was found the ETDA Tool provides reasonable agreement with the field damage observations to houses. The Tool could be used by a community to model any tornado path and/or size and estimate future damage. More research to further our understanding of tornado-induced wind loads and wind-borne debris effects are needed to increase confidence in its application to any tornado and any city.